1992
DOI: 10.1111/j.1365-2249.1992.tb06464.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of spontaneous and cyclophosphamide-induced diabetes in non-obese diabetic (NOD) mice with oral 2-acetyl-4-tetrahydroxybutyIimidazole (THI), a component of caramel colouring III

Abstract: SUMMARY The effect of oral administration of THI, a compound present in ammonia caramel food colouring, was studied in spontaneous and induced murine diabetes mellitus. Continuous administration of THI at400 ppm in drinking water reduced the prevalence of spontaneous diabetes in female NOD/Lt mice from 63% in untreated controls to 8% in treated animals. Since cyclophosphamide (CP) accelerates and intensifies diabetes in NOD mice, we also studied the effect of THI in this model. Diabetes incidence was reduced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The effect of oral administration of THI was studied in spontaneous and induced murine diabetes mellitus (Mandel et al, 1992). Continuous administration of THI at 400 mg/kg in drinking water reduced the prevalence of spontaneous diabetes in female NOD/Lt mice from 63% in untreated controls to 8% in treated animals.…”
Section: Annex Bmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of oral administration of THI was studied in spontaneous and induced murine diabetes mellitus (Mandel et al, 1992). Continuous administration of THI at 400 mg/kg in drinking water reduced the prevalence of spontaneous diabetes in female NOD/Lt mice from 63% in untreated controls to 8% in treated animals.…”
Section: Annex Bmentioning
confidence: 99%
“…However, there was moderate atrophy of the thymus cortex. The authors concluded that THI could be a useful immunosuppressive agent (Mandel et al, 1992).…”
Section: Annex Bmentioning
confidence: 99%
“…THI produces lymphopenia, apparently without toxic effects, in rats and mice and is able to affect the immune competence in the rat in quite small quantities (e.g., 1−50 ppm in drinking water) . THI has also been reported to prevent spontaneous and cyclophosphamide-induced diabetes in non-obese diabetic mice . To investigate the structure−activity relationships of this structurally simple but biologically intriguing molecule, we desired a general and flexible synthesis of THI analogues.…”
Section: Introductionmentioning
confidence: 99%